Transcriptional response of endometrial cells to insulin, cultured using microfluidics - Soo Young Baik; Alisha Miani; Haidee Tinning; Dapeng Wang; Daman J Adlam; Peter T Ruane; Niamh Forde (Bioscientifica, 2023)
Obesity is a rapidly growing public health issue among women of reproductive age associated with decreased reproductive function including implantation failure. This can result from a myriad of factors including impaired gametes and endometrial dysfunction. The mechanisms of how obesity-related hyperinsulinaemia disrupts endometrial function are poorly understood. We investigated potential mechanisms by which insulin alters endometrial transcript expression. Ishikawa cells were seeded into a microfluidics device attached to a syringe pump to deliver a constant flow rate of 1 μL/min of the following: (i) control (ii) vehicle control (acidified PBS), or (iii) insulin (10 ng/mL) for 24 h (n = 3 biological replicates). Insulin-induced transcriptomic response of endometrial epithelial cells was determined via RNA sequencing, and DAVID and Webgestalt to identify Gene Ontology (GO) terms and signalling pathways. A total of 29 transcripts showed differential expression levels across two comparison groups (control vs vehicle control; vehicle control vs insulin). Nine transcripts were differentially expressed in vehicle control vs insulin comparison (P < 0.05). Functional annotation analysis of transcripts altered by insulin (n = 9) identified three significantly enriched GO terms: SRP-dependent co-translational protein targeting to membrane, poly(A) binding, and RNA binding (P < 0.05). The overrepresentation analysis found three significantly enriched signalling pathways relating to insulin-induced transcriptomic response: protein export, glutathione metabolism, and ribosome pathways (P < 0.05). Transfection of siRNA for RAPSN successfully knocked down expression (P < 0.05), but this did not have any effect on cellular morphology. Insulin-induced dysregulation of biological functions and pathways highlights potential mechanisms by which high insulin concentrations within maternal circulation may perturb endometrial receptivity.